Assessing the Economic Impact of the Pantawid Pamilyang Pilipino Program (4Ps) in the Philippines : A Systematic Review - Diaz, Jayson (Universitas Dinamika, 2025)
This systematic review examines the impact of the Pantawid Pamilyang Pilipino Program (4Ps) on poverty reduction, education, healthcare utilization, and economic stability in the Philippines. Following the preferred reporting items for systematic reviews and meta analyses (PRISMA) guidelines, this study synthesizes findings from peer reviewed articles, government reports, and policy papers. Results indicate that 4Ps has significantly improved school enrollment, healthcare access, and household consumption, contributing to overall human capital development. However, challenges persist, including program dependency, targeting inefficiencies, misallocation of grants, and gaps in healthcare service utilization. Comparative analysis highlights regional disparities, with rural beneficiaries benefiting more from education and health services, while urban households demonstrate better financial management. Thematic synthesis reveals that employment effects remain mixed, as male household members show increased labor participation, whereas female employment remains unchanged. Policy recommendations emphasize strengthening livelihood programs, improving grant monitoring, addressing targeting inefficiencies, and enhancing family development sessions (FDS) for long-term socio-economic impact. While 4Ps has contributed to poverty alleviation and social mobility, continued refinements in program implementation, inter-agency coordination, and financial sustainability are necessary to maximize its long-term impact. Future research should explore longitudinal assessments and alternative social protection mechanisms to improve the program’s effectiveness.